Impact of Liver and Kidney Function on Vitamin D3 Metabolism in Female and Male Patients Undergoing Allogeneic Hematopoietic Stem-Cell Transplantation - Weich, Laura; Brummer, Christina; Ghimire, Sakhila; Peter, Katrin; Althammer, Michael; Babl, Nathalie; Voll, Florian; Bruss, Christina; Hoering, Marcus; Wallner, Stefan; Siska, Peter J.; Holler, Ernst; et al. (International Journal of Molecular Sciences, 2025)
We previously described that elevated levels of the active vitamin D3 metabolite 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) during the early phase of allogeneic hematopoietic stem-cell transplantation (HSCT) can predict one-year transplant-related mortality (1y-TRM). Given that the liver and kidneys are the primary organs responsible for the effective conversion of vitamin D3, we investigated whether liver and/or kidney function, inflammation, or patient sex might influence vitamin D3 metabolism and, consequently, patient outcomes during transplantation. We found that female patients exhibited higher levels of 1,25(OH)2D3 at the time of transplantation compared with male patients. However, 1,25(OH)2D3 levels were associated with 1y-TRM in both sexes. No correlation was found between liver-associated markers, such as bilirubin, or the inflammation marker C-reactive protein (CRP) and serum levels of vitamin D3 metabolites in either female or male patients. However, serum levels of 1,25(OH)2D3, but not 25(OH)D3 correlated with the creatinine-based estimated glomerular filtration rate (eGFR), indicating that 1,25(OH)2D3 levels are associated with kidney function in HSCT patients. However, a Cox regression analysis, adjusted for baseline risk factors, demonstrated that high peri-transplant levels of 1,25(OH)2D3 (measured from days −2 to 7) remained a significant predictor of patient survival, even when eGFR was taken into account (hazard ratio = 0.99; p = 0.004). These findings suggest that optimal serum levels of 1,25(OH)2D3 may not be achievable in some HSCT patients and that kidney function alone cannot explain why some patients fail to reach the optimal 1,25(OH)2D3 threshold. These data support the potential use of 1,25(OH)2D3 as a prophylactic agent, particularly in patients with pre-existing kidney disease.
CRIS-Team Scopus Importer:2025-04-18
Keywords: 1; 25(OH); 25(OH)D3 2; bilirubin; eGFR; GvHD; HSCT; vitamin D3